Profiling of bioactive compounds in Malaysian herbs - Haron, Normah; Tan, Teng Ju (2018)
This study profiled selected phenolic acids, quantified total phenolic content (TPC) and antioxidant activities of five herbal plants namely Citrus hystrix, Coriandrum sativum, Murraya koenigii, Polygonum minus and Ocimum basilicum in phenolic fractions of free, soluble bound and insoluble bound. The TPC was quantified using Folin-Ciocalteu method and phenolic acids were detected using high performance liquid chromatography (HPLC). The antioxidant activities were determined using 2, 2-Diphenyl-1-picrylhydrazyl (DPPH) and 2, 2’-Azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) assays. The result showed that gallic acid, caffeic acid, ferulic acid, sinapinic acid and p-coumaric acid were detected in distinctive proportion. For majority of plants, phenolic acids extracted from soluble and insoluble bound phenolic fractions had higher concentrations compared to free phenolic fraction. Of the plants tested, P. minus and O. basilicum showed higher total phenolic content and promising antioxidant activities in DPPH and ABTS assays. These antioxidant capabilities can be correlated with the presence of phenolic acids. In fact, there were strong correlation between TPC and both antioxidant assays. The significance of this study could be of important relevant in providing information of polyphenols composition and radical scavenging activity in various herbal plants.